TEKNIK PENGOLAHAN SELAI TOMAT SEBAGAI MEDIA BELAJAR DAN DUKUNGAN BAGI UMKM PANGAN LOKAL DI SMA KRISTEN PONTAK, MINAHASA SELATAN - Melpin, Rostina; Dusun, Citra; Mandang, Filan O; Lomo, Christine P; Aida, Yuannita (LPPM Universitas Ibnu Sina, 2026)
The Community Service Program (CSP) on tomato jam processing techniques at SMA Kristen Pontak, South Minahasa, was implemented as a solution to the abundant tomato harvests that are often not absorbed by the market, reducing farmers’ economic value. The main problems faced by partners include limited knowledge of product diversification, food hygiene standards, and basic marketing strategies. The objective of this program is to improve the skills of students, teachers, and local MSMEs in processing tomatoes into hygienic, durable, and marketable jam products, while strengthening collaboration between schools and communities in local economic empowerment. The method applied was a participatory approach through five stages: preparation, socialization, training and demonstration, mentoring implementation, and evaluation and dissemination. Evaluation was conducted using pre-test and post-test to measure improvements in participants’ knowledge and skills. Results showed significant progress, with the average pre-test score of 57 increasing to 82 in the post-test, reflecting a 44% improvement. The highest increase was observed in simple marketing strategies, rising from 50 to 78 (a 56% gain), followed by food hygiene from 55 to 80, and processing techniques from 58 to 83. The program successfully produced trial tomato jam products with simple yet marketable packaging and established collaborative networks between schools and MSMEs. Overall, this initiative provided positive impacts in education through practice-based learning and strengthened the capacity of local food MSMEs, serving as a replicable model for entrepreneurship development based on local resources.